Diatoms as bioindicators of pollution in the Mantaro River, Central Andes, Peru. (6th June 2008) - Tapia, Pedro M.
Semi-quantitative analysis of two algal samples from the Mantaro River taken few kilometres downstream from La Oroya city at Junin, Peru, contained both organic-pollution tolerant and morphologically abnormal diatom associations. The organic pollution is inferred by elevated percentages of Nitzschia palea, Gomphonema parvulum and the Achnanthidium minutissimum complex; the total assemblage indicates an oligosaprobic to α-mesosaprobic status. A distinctive subset of diatom valves shows abnormal outline morphology and ornamentation deformities in several individuals of the species Achnanthidium macrocephalum, Cymbella hustedtii, Diatoma moniliformis, Encyonema silesiacum, Surirella minuta, Synedra acus, Synedra rumpens, Synedra ulna and Synedra vaucheriae. Abnormal diatom ornamentation and morphology is usually associated to elevated concentration of heavy metals (Cr, Cd, Cu, Zn, Sr) in aquatic ecosystems. Therefore, the Mantaro River at this site contained a low water quality based on diatom bioindicators of organic and heavy metal pollution.